Knowledge and attitude of human Mpox viral infection among pharmacy students in Jazan University: a web based cross-sectional study - Ali, Eman Merghani; Khardali, Amani; Alam, Nawazish; Meraya, Abdulkarim M.; Thaibah, Hilal A.; Hassan, Dalin A.; Elmobark, Mohamed Eltaib; Aladwani, Alanood; Mohanan, Anugeetha Thacheril; Bakri, Hanan A.; Mashraqi, Zamzam O.; Salhabi, Areej Mousa (Frontiers in Public Health, 2025)
IntroductionSaudi Arabia has witnessed the first confirmed case of Mpox on July 14th, 2022. Currently, there is no approved medication for the treatment of this infection. Therefore, prevention of this infection is crucial. This study aimed to assess knowledge and attitude toward the monkeypox viral infection among pharmacy students of Jazan University in Saudi Arabia.MethodsThis is a cross-sectional, self-administered web-based study between the periods from April 2024 to June 2024. Descriptive statistics for all variables used chi-square statistics, and multivariate analysis to establish the association between participant’s demographic characteristics and knowledge of monkeypox disease.ResultsThe overall level of knowledge and attitude found 32 and 44.5%, respectively among pharmacy students. The source of information was commonly social media (55.5%), and only 38% reported receiving information during medical education. The factors associated with knowledge level included gender (p = 0.02), obesity (p = 0.03), receiving information from family or friends (p = 0.03), and during medical education (p = 0.016). The factors that were associated with attitude included age (p = 0.03), chronic disease (p = 0.0001), social media (p = 0.007), and medical education (p = 0.004) as sources of information.ConclusionThis study found the participants had a low level of knowledge and attitude toward Mpox infection. There is a need for the implementation of educational programs to know about this kind of outbreak and increase the knowledge and attitude of the students.